War and Society in 19th Century: A short overview - Hutecka, Jiri (Historica Olomucensia, 2010)
The purpose of this article is to summarize the process of change as it developed in European warfare during the ``long'' 19th century. As it is impossible to make a deep analysis of the whole problem in such a short space, the text is much more of a general survey, with necessary albeit important omissions of the non-European warfare, including the colonial experience. At the beginning, a starting point for the whole essay is established with survey of war in the so-called Age of Reason. Connection between war and society as well as military thinking and theories (the so-called ``military enlightenment'') are given the primary attention. Then, the flow of text follows three main lines of change occurring in the 19th century. First, it is the line of ideas, with introduction of ideological motivation and modern citizenship on the one hand, and with the so-called ``military romanticism'' (epitomized by Clausewitz) in military theory on the other. Second, changes in institutional structure of warfare are followed, with primary emphasis on the shift from a long-service regular army towards mass army based on a system of reserves, along with its dire consequences in terms of militarization of society. Also, development of general staff is followed briefly. Last but not least, development in technology and its consequences for warfare is followed in the third part, with emphasis on ``civilian'' technologies more than on weapon systems. All these lines are invariably interconnected and only through their understanding, it is possible to get a clear picture of warfare in 19th century. It is also further argued that the European tragedy of the Great War was only a natural result of this historical process.